2011
DOI: 10.1098/rstb.2010.0376
|View full text |Cite
|
Sign up to set email alerts
|

How copying affects the amount, evenness and persistence of cultural knowledge: insights from the social learning strategies tournament

Abstract: Darwinian processes should favour those individuals that deploy the most effective strategies for acquiring information about their environment. We organized a computer-based tournament to investigate which learning strategies would perform well in a changing environment. The most successful strategies relied almost exclusively on social learning (here, learning a behaviour performed by another individual) rather than asocial learning, even when environments were changing rapidly; moreover, successful strategi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
54
1

Year Published

2011
2011
2020
2020

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 59 publications
(56 citation statements)
references
References 41 publications
1
54
1
Order By: Relevance
“…They found that increased migration hinders social learning and pointed to the importance of population structure on the evolution of social learning. In contrast, the simulation approach of the 'social learning strategies tournament' suggested that social learning could be more effective than asocial learning even when environments change rapidly [29,30]. These differences relate, in part, to whether multiple traits are considered (as in the tournament), which allows social learners to adjust their behaviour flexibly following environmental change, switching between the variants in their repertoire to maintain adaptive behaviour.…”
Section: Introductionmentioning
confidence: 90%
“…They found that increased migration hinders social learning and pointed to the importance of population structure on the evolution of social learning. In contrast, the simulation approach of the 'social learning strategies tournament' suggested that social learning could be more effective than asocial learning even when environments change rapidly [29,30]. These differences relate, in part, to whether multiple traits are considered (as in the tournament), which allows social learners to adjust their behaviour flexibly following environmental change, switching between the variants in their repertoire to maintain adaptive behaviour.…”
Section: Introductionmentioning
confidence: 90%
“…We might focus on the function of heterogeneity in how people make decisions, particularly the balance of individual learning, which produces information, and social learning, which diffuses and exploits that information [10,17,18]. All too often, however, observational data alone fail to distinguish not only between social learning and individual learning, but also between social learning and homophily-the tendency for people with similar traits to co-associate [19,20].…”
Section: Introductionmentioning
confidence: 99%
“…Strategies that fared most successfully in mastering the exploitation of an initially unknown environment were found to rely strongly on social learning. Here, Rendell et al [35], extend this work to examine the wider implications of different learning strategies for cultural evolution. Drawing a distinction between effects on individuals' knowledge versus the behaviour they express, Rendell et al discover intriguing differences in the effects of a heavy reliance on cultural transmission on these two factors, which together confer adaptive plasticity in relation to environmental change.…”
Section: Human Culture Evolves and Diversifies: How Darwinian Is Cultmentioning
confidence: 99%
“…This and the animal social foraging literature [70] have emphasized the frequencydependent quality of social learning. Social learning can be viewed as 'information parasitism' and accordingly, some balance of social learning (information 'scrounging') and asocial learning ('information producing') is expected in a population (but see Rendell et al [35], for a counter perspective). This and other theoretical reasons for why social learning might not be expected to be as common in nature as some of the above considerations might predict are set out by Rieucau & Giraldeau [1] in the opening paper of part 1.…”
Section: Culture Evolves In the Animal Kingdommentioning
confidence: 99%
See 1 more Smart Citation